Generation Z - Their Perception of Work and work culture - Dr. Ritu Bhattacharyya, Dr. Sangita Kohli, Dr. Rupali More, Vaishali Kothiya (International Journal of Advanced Science and Technology, 2020)
Generation Z’s are defined as those who were born in or after 2000, this generation is maximum 19 years old, but that does not mean that they are not part of the work force. No generation before this believed in internships and online work as much as them. Many of them have been on internships right since they were 15-16 years old. They possesses a mindset which is very different from the previous generations. Many of their parents would want them to complete their studies before they look for employment opportunities but most of the Generation Z would like to be very sure of what they want to do before they finish their basic studies so that they can acquire the skills required for their dream jobs, and do not want to waste their time in basic degrees that will not get them anywhere. Not only are their expectations for the education system very different but their expectations from their potential employers is also very different. They are not like any of the earlier generations because they were born into a digital world. Everyone in this generation is digital savvy, the CEO’s child may have several digital devices but the peons child will have a smart phone with an internet facility thus reducing the gap of facilities available. The generation has very little respect for formal education, but at the same time realise that skills are important and communication is important. The paper aims to find out the characteristics of Generation Z and their perception towards work and work culture.